Adaptive capability of micro agribusiness firms: Qualitative evidence from the Philippines. (December 2022) - Isip, Marc Immanuel G.
Abstract: Handicraft production is seen to be a promising opportunity to provide sustainable productive employment in the rural areas of the Philippines. The full implementation of the Regional Comprehensive Economic Partnership opened opportunities for bigger international market but ushered in tougher challenges; this study aims to explore the concept of adaptive capability of micro handicraft firms in response to effects brought by this economic and trade agreement. Semi-structured, in-depth interviews with eight owner-managers, and two separate focus group discussions composed of six owner-managers of micro agricultural handicraft firms was conducted. Thematic analysis yielded three characteristics of adaptive capability: 1) value creation through product and process improvement complemented with customer service, 2) organizational agility and flexibility in decision making through their skilled and knowledgeable workforce with the use of available information, and 3) organizational resourcefulness to tap into the services provided by institutions and into online platforms provided by telecommunication infrastructure for product placement and promotion. These characteristics enable these firms to make necessary actions, decisions, and strategies which are dynamic and adaptive to the trade environment. However, they are facing hardships in terms of prioritization and inclusiveness in the value chain; sources of financial capital, access to technology and information are among the important factors to develop their adaptive capability. This study's original contribution to knowledge is the hierarchical thematic framework of adaptive capability and that the methodology used has uncovered underlying indirect factors that may be considered mediators that add depth to the understanding of the concept of adaptive capability.